Evodiamine suppresses the progression of non-small cell lung carcinoma via endoplasmic reticulum stress-mediated apoptosis pathway in vivo and in vitro. (6th April 2022) - Li, Yuting; Wang, Yuming; Wang, Xiaoqun; Jin, Lulu; Yang, Lu; Zhu, Jinli; Wang, Hongwu; Zheng, Fang; Cui, Huantian; Li, Xiaojiang; Jia, Yingjie
Background: Evodiamine (EVO) is one of the major components isolated from Evodia rutaecarpa (Juss.). Recent studies have shown that EVO has an anti-cancer effect. However, the pharmacological mechanism by which EVO impacts cancer is still poorly understood. Objectives: This study focused on asking the anti-cancer effect of EVO in human non-small cell lung carcinoma (NSCLC), and in particular to investigate whether EVO acts via modulating the endoplasmic reticulum stress (ERS)-mediated apoptosis pathway. Materials and Methods: A Lewis lung carcinoma (LLC) tumor-bearing mouse model was treated with low-dose EVO (5 mg/kg) and high-dose EVO (10 mg/kg) intraperitoneally for 14 d. The effects of EVO on tumor growth, apoptosis, and ERS were assessed. In addition, NSCLC A549 and LLC cells were treated with EVO in vitro. The effects of EVO on cell proliferation, apoptosis, and ERS were investigated. Finally, 4-phenylbutyric acid (4-PBA), an ERS inhibitor, was used to validate whether EVO induced apoptosis of NSCLC cells by modulating ERS. Results: EVO treatment significantly inhibited tumor growth in LLC tumor-bearing mice. H&E staining indicated that EVO treatment reduced the number of tumor cells and the nucleo-plasmic ratio. Immunostaining showed that EVO treatment significantly decreased the expression of Ki-67. TUNEL staining revealed that EVO induced apoptosis in the tumor. Likewise, EVO treatment up-regulated the expression of apoptosis-related genes and proteins and increased activation of the ERS pathway in the tumor. Additionally, EVO inhibited cell proliferation and increased cell apoptotic rates in A549 and LLC cells. EVO also increased the expression levels of genes and proteins associated with ERS-mediated apoptosis pathway in vitro. The effects of EVO on apoptosis were abolished by 4-PBA treatment. Conclusions: Our study demonstrated that EVO suppresses the progression of NSCLC by modulating the ERS-mediated apoptosis pathway.